Exome sequencing of pashtun familial epilepsy in Pakistan reveals novel variants in LAMA5, KCNQ2 and GNAO1 - Qaisar Ali; Sadiq Azam; Jamila Javed; Muhammad Zaheer; Saqib Ullah; Aqib Iqbal; Ibrar Khan; Shoaib Ur Rehman (Molecular Biology Reports, 2026)

Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

EPIGENETIC REDUCTION OF H3K9me3 AND H3K27me3 BY RK-701 AND GSK 126 IMPROVES THE DEVELOPMENTAL COMPETENCE OF BOVINE SCNT EMBRYOS - Deborah Onosetale; Zaheer Haider; Chalani Dilshani Perera; Safeer Ullah; Seo-Hyun Lee; Seung-Eun Lee; Jihyo Kim; Min-Ju Lee; Muhammad Idrees; Il-Keun Kong (Theriogenology, 2026)

Dihydroxyflavones as potential therapeutic agents against inflammation and renal injury via p38 MAP kinase inhibition: an in silico and experimental study - Farwa Naqvi; Almas Jabeen; Muhammad Shafiq; Shaheen Faizi; Zaheer Ul-Haq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Synergistic donnan exclusion and size sieving strategy in layered double hydroxide modified nanofiltration membranes for superior desalination performance - Muhammad Zaheer Afzal; Yanling Chen; Zeping Pei; Yunkun Wang (Desalination, 2026)

Assessment of groundwater quality and fluoride health risks using multimetric indices in Balochistan, Pakistan - Muhammad Zaheer; Waqar Azeem Jadoon; Memet Varol; Ibraheem Khan; Abu Reza Md Towfiqul Islam (Journal of Environmental Chemical Engineering, 2026)

Entropy generation in electroosmotic cilia-induced Jeffrey fluid flow through an axisymmetric tube with slip effects - Muhammad Yousuf Rafiq; Zaheer Abbas; Hafiz Shahzad; Sharia Bashir (Dynamics of Atmospheres and Oceans, 2026)

RETRACTED ARTICLE: Modification of a nonlinear transfer-function noise model for the estimation of groundwater recharge - Saad Zaheer; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem (Hydrogeology Journal, 2026)

Traditional plant-based therapies in the Trans-Himalayan Cold deserts of Baltistan, Northern Pakistan - Zaheer Abbas; Shazia Kousar; Muhammad Uzair; Samuel Kelly Rees; Arshia Zia (Plant Biosystems, 2026)

Computational exploration of Aegle marmelos coumarins: DFT, molecular docking, and dynamics studies for anti-hypertensive activity - Jan Alam; Muhammad Ali Versiani; Nadeem Ahmed; Syed Intasar Husain Taqvi; Syed Tahir Ali; Zaheer Ul-Haq (Natural Product Research, 2026)

Validating the Efficiency of the AquaCrop Model Under Full and Deficit Irrigation Regimes to Simulate Future Climate Impacts on Wheat Crop - Shamim Ara Memon; Irfan Ahmed Shaikh; Mashooque Ali Talpur; Abdul Rahim Junejo; Munir Ahmed Mangrio; Nazar Gul; Zaheer Ahmed Khan; Hafiz Abdul Salam; Muhammad Ashraf (Irrigation and Drainage, 2026)
Wheat yield and water demand are affected by the ongoing disturbance of climatic factors and greenhouse gases (GHG). As a result, the AquaCrop model's ability to anticipate climate change impacts on wheat harvests under full and deficit irrigation regimes in Sindh, Pakistan, was evaluated using wheat trials conducted between 2018 and 2020. However, for its validation, the results of the deficit irrigation treatment ITS 50 (50% controlled irrigation at the tillering stage) for both seasons were employed. The model efficiently estimated yield with a normalised root‐mean‐square error (NRMSE) of 13% and 17%, a Willmott's d ‐index of 98% and a Nash–Sutcliffe efficiency (NME) of 95% under full and deficit irrigation treatments, respectively. The simulation results revealed an adverse effect of climate change on the yield and water productivity of wheat. Over the century, the model predicted an increase of 6% to 7% in wheat yield under full (well‐watered) irrigation and a decrease of 10 to 12% in 25% reduced water applied depth (RAD) and 21% to 24% under 50% RAD scenarios for both representative concentration pathway RCPs (4.5 and 8.5). The overall wheat water productivity increased under a well‐watered irrigation regime by 16% in RCP8.5 compared with RCP4.5.

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nonlinear analysis of thermo-magneto slip flow of Jeffery fluid in a wavy curved channel - Maham Mujahid; Mounirah Areshi; Zaheer Abbas; Muhammad Yousuf Rafiq; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

A toolkit for the assessment of training needs and gaps of the national Veterinary Services in field epidemiology - Imadidden Musallam; Julio Pinto; Ravi Bandara Dissanayake; Muhammad Usman Zaheer; Zaidoun Hijazeen; Wafa’a Ramadneh; Iqbal Qatananni; Esam Hawa; Majed Hawaowsheh; Ehab Abu-Basha; Aida binti Muhid; Jamaliah binti Senawi; et al. (The Veterinary Journal, 2026)

Bovine mastitis and antimicrobial resistance in Pakistan’s dairy sector: current status and future prospects - Nauman Zaheer Ghumman; Mieghan Bruce; Amanda Duarte Barbosa; Muhammad Ijaz; Jiaxin Peng; Jully Gogoi-Tiwari (Veterinary Research Communications, 2026)
Bovine mastitis remains one of the most widespread and economically significant diseases affecting the dairy sector in Pakistan. Despite being a leading global milk producer, Pakistan’s dairy industry faces persistent challenges in controlling mastitis, particularly among smallholder farmers with limited access to veterinary care and diagnostic tools. Antibiotics are frequently used to manage mastitis, often without veterinary oversight, contributing to the growing concern of antimicrobial resistance (AMR). The widespread presence of Staphylococcus aureus , a biofilm-forming pathogen, further complicates treatment and accelerates resistance development. Pakistan has initiated efforts to address AMR through national action plans. However, gaps remain in surveillance, responsible antibiotic use, and access to affordable alternatives. This review examines the current landscape of bovine mastitis in Pakistan, including its epidemiology, economic impact, therapeutic practices, and AMR trends. It also outlines practical, low-cost recommendations for improving mastitis management and reducing inappropriate use of antibiotics, particularly in rural settings. Addressing these interconnected challenges through locally adapted, sustainable approaches is essential for improving animal health, milk safety, and long-term productivity in Pakistan’s dairy sector, whilst addressing the global challenge of AMR.

Root microstructural traits regulate ion homeostasis in bush morning glory (Ipomoea carnea Jacq.) for invasiveness success in saline environments - Syed Mohsan Raza Shah; Naila Hadayat; Jazab Shafqat; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Maham Zia; Zaheer Abbas; Zahida Parveen; Muhammad Ashraf; Ummar Iqbal; Ansa Asghar; et al. (The Science of Nature, 2026)

The interplay of urban landscape and PM2.5 exposure disparities: A machine learning approach in Shandong, China - Rizwan Muhammad; Zaheer Abbas; Jiuru Wang (Environmental Research, 2026)

Rhodanine-benzamides as potential hits for α-amylase enzyme inhibitors and radical (DPPH and ABTS) scavengers - Samuel Attah Egu; Irfan Ali; Khalid Mohammed Khan; Sridevi Chigurupati; Urooj Qureshi; Uzma Salar; Zaheer Ul-Haq; Suliman A. Almahmoud; Shatha Ghazi Felemban; Mohsin Ali; Muhammad Taha (Molecular Diversity, 2025)

Roles of Fox gene in the development and reproduction of diamondback moth - Anam Noreen Abbas; Mubashir Tariq; Faisal Munir; Uroosa Zaheer; Ibrahim Adam; Muhammad Asad; Guang Yang (Journal of Insect Physiology, 2025)

Computational exploration of aphrodisiac potential: identifying inhibitors from Tribulus terrestris L., and Securidaca longepedunculata targeting human phosphodiesterase 5 - Sikiru Akinyeye Ahmed; Ali Agaka Aremu; Muhammad Shafiq; Zaheer Ul-Haq (In Silico Pharmacology, 2025)

Evaluation of chalcones as new glycogen phosphorylase inhibitors – an in-vitro and in-silico approach - Talal Ahmed Awad; Fatima Alfatih; Muhammad Shafiq; Mohnad Abdalla; Samia T. Al-Shouli; Amani Bashir; Maaweya E. Awadalla; Hassan A. Alhazmi; Mohammed Albratty; Hafiz A. Makeen; Asaad Khalid; Zaheer Ul-Haq (Natural Product Research, 2025)

Energy bandgap tuning of Sr-doped ZnO nanoparticles for photodegradation of azo dyes and antibacterial applications - Hufsa Ahmad; Abu Bakar Siddique; Saima Zaheer; Rabia Sattar; Azhar Abbas; Muhammad Amin; Rashad Al-Salahi; Hatem A. Abuelizz; M. Zubair Saleem (Journal of Water Process Engineering, 2025)

Explainable artificial intelligence-based compressive strength optimization and Life-Cycle Assessment of eco-friendly sugarcane bagasse ash concrete - Varisha Rizwan; Syed Muhammad Ibrahim; Mohd Moonis Zaheer; Ateekh ur Rehman (Environmental Science and Pollution Research, 2025)

Assessing the influence of eucalyptus bark ash and willow wood ash on the physical, mechanical, and microstructural properties of portland cement pastes and mortars - Nazeef Ullah; Muhammad Hanif Khan; Muhammad Ali Sikandar; Zhao Qiuhong; Han Zhu; Obaid Rauf; Zaheer Farooq (Innovative Infrastructure Solutions, 2025)

Application of Magnetically Recoverable Biochar Amended Zirconium Adsorbent Composite for Enhanced As(III, V) Removal from Aqueous Solutions - Imdad Ullah; Shams Ali Baig; Harsa Zaheer; Dilawar Farhan Shams; Hamida Bibi; Waliullah Khan; Xinhua Xu; Muhammad Danish (Water, Air, & Soil Pollution, 2025)

Foot-and-mouth disease virus dynamics in border areas of Pakistan with Afghanistan - Abdul Kabir; Asghar Ali Kamboh; Muhammad Abubakar; Hasina Baloch; Zaheer Ahmed Nizamani (Molecular Biology Reports, 2024)

Recombinant expression, downstream optimization, and therapeutic evaluation of recombinant human interleukin-37 for cancer therapy - Zaheer Abbas; Samia Afzal; Nao Akusa Fujimura; Muhammad Akram; Saad Tahir; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2024)

Periodate-driven efficient degradation of diverse pharmaceuticals with iodine-doped MnO2 - Muhammad Zaheer Afzal; Hao Zhang; Hongkui He; Jintong Ma; Liming Qin; Yunkun Wang (Chemical Engineering Journal, 2024)

Proximate composition and prevalence and exposure assessment of aflatoxins intake through consumption of fresh carrot and processed marketed carrot products in South Punjab, Pakistan - Aneela Nijabat; Shahwana Bibi; Maryam Ajmal; Saher Nawaz; Muhammad Zaheer Sajid; Saad Ullah Khan Leghari; Muhammad Mahmood-ur-Rehman; Naima Huma Naveed; Aamir Ali; Philipp W. Simon (Natural Product Research, 2024)

Detection of Mobile and Immobile Solute Transport and Their Residence Time in Saturated Low and High Permeability Soil Layers - Muhammad Zaheer; Ehsan Ul Haq; Ning Huang; Ahmed Amara Konaté; Ghulam Mujtaba Shah; Raja Umer Sajjad; Saad Ahmed Mashwani (Water, Air, & Soil Pollution, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Environmental influences on soil phosphorus dynamics and eutrophication risks in the Three Gorges reservoir Area, Chongqing section - Wenyu Qi; Ting Li; Shirong Zhang; Wenshu Kuang; Guiyin Wang; Zhe Wang; Chao Song; Xiaoxun Xu; Yulin Pu; Muhammad Zaheer Afzal; Shuguang Wang (CATENA, 2024)

Green synthesis of silver nanoparticles for antifungal activity against tomato fusarium wilt caused by Fusarium oxysporum - Raja Zaheer Tabassum; Ansar Mehmood; Abd ur Rehman Khalid; Khawaja Shafique Ahmad; Muhammad Abdul Rauf Khan; Muhammad Shoaib Amjad; Muhammad Raffi; Gull-e-laala Khan; Amna Mustafa (Biocatalysis and Agricultural Biotechnology, 2024)

A deep learning-based theoretical protocol to identify potentially isoform-selective PI3Kα inhibitors - Muhammad Shafiq; Zaid Anis Sherwani; Mamona Mushtaq; Mohammad Nur-e-Alam; Aftab Ahmad; Zaheer Ul-Haq (Molecular Diversity, 2024)

Assessment of hydrochemical characteristics, health risks and quality of groundwater for drinking and irrigation purposes in a mountainous region of Pakistan - Waqar Azeem Jadoon; Muhammad Zaheer; Abdul Tariq; Raja Umer Sajjad; Memet Varol (Environmental Science and Pollution Research, 2024)
Renowned for its agriculture, livestock, and mining, Zhob district, Pakistan, faces the urgent problem of declining groundwater quality due to natural and human-induced factors. This deterioration poses significant challenges for residents who rely on groundwater for drinking, domestic, and irrigation purposes. Therefore, this novel study aimed to carry out a comprehensive assessment of groundwater quality in Zhob district, considering various aspects such as hydrochemical characteristics, human health risks, and suitability for drinking and irrigation purposes. While previous studies may have focused on one or a few of these aspects, this study integrates multiple analyses to provide a holistic understanding of the groundwater quality situation in the region. Additionally, the study applies a range of common hydrochemical analysis methods (acid–base titration, flame atomic absorption spectrometry, and ion chromatography), drinking water quality index (WQI), irrigation indices, and health risk assessment models, using 19 water quality parameters. This multi-method approach enhances the robustness and accuracy of the assessment, providing valuable insights for decision-makers and stakeholders. The results revealed that means of the majority of water quality parameters, such as pH (7.64), electrical conductivity (830.13 μScm –1 ), total dissolved solids (562.83 mgL –1 ), as well as various anions, and cations, were in line with drinking water norms. However, the water quality index (WQI) predominantly indicated poor drinking water quality (range = 51–75) at 50% sites, followed by good quality (range = 26–50) at 37% of the sites, with 10% of the sites exhibiting very poor quality (range = 76–100). For irrigation purposes, indices such as sodium percent (mean = 31.37%), sodium adsorption ratio (mean = 0.98 meqL –1 ), residual sodium carbonate (– 3.15 meqL –1 ), Kelley’s index (mean = 0.49), and permeability (mean = 49.11%) indicated suitability without immediate treatment. However, the magnesium hazard (mean = 46.11%) and potential salinity (mean = 3.93) demonstrated that prolonged application of groundwater for irrigation needs soil management to avoid soil compaction and salinity. Water samples exhibit characteristics of medium salinity and low alkalinity (C2S1) as well as high salinity and low alkalinity (C3S1) categories. The Gibbs diagram results revealed that rock weathering, including silicate weathering and cation exchange, is the primary factor governing the hydrochemistry of groundwater. The hydrochemical composition is dominated by mixed Ca–Mg–Cl, followed by Na–Cl and Mg–Cl types. Furthermore, the human health risk assessment highlighted that fluoride (F – ) posed a higher risk compared with nitrate (NO 3 – ). Additionally, ingestion was found to pose a higher risk to health compared to dermal contact, with children being particularly vulnerable. The average hazard index (HI) for children was 1.24, surpassing the allowable limit of 1, indicating detrimental health effects on this subpopulation. Conversely, average HI values for adult females (0.59) and adult males (0.44) were within safe levels, suggesting minimal concerns for these demographic groups. Overall, the study’s interdisciplinary approach and depth of analysis make a significant contribution to understanding groundwater quality dynamics and associated risks in Zhob district, potentially informing future management and mitigation strategies.

Highly efficient nickel recovery from industrial wastewater via synergistic electrodeposition and electrocatalytic oxidation technique - Muhammad Akram; Zahira Bano; Seerat Ul Ain Bhutto; Jingwen Pan; Ahmed Uddin; Muhammad Zaheer Afzal; Linrui Li; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Tourism triumphs: unraveling the essence of Asia’s allure through governance, FDI, and natural bounties - Muhammad Zaheer Akhtar; Khalid Zaman; Muhammad Azhar Khan (Journal of Environmental Studies and Sciences, 2024)

Phytoremediation of heavy metal-contaminated soil of Lyari River using bioenergy crops - Musarrat Ramzan; Saira Sarwar; Muhammad Zaheer Ahmad; Rifat Zubair Ahmed; Tanveer Hussain; Iqtidar Hussain (South African Journal of Botany, 2024)

Effect of additional cytoplasm injection on the cloned bovine embryo organelle distribution and stress mitigation - Ji-Su Kang; Myeong-Don Joo; Seo-Hyeon Lee; Seon-Min Kang; Zaheer Haider; Chalani Dilshani Perera; Muhammad Idrees; Yongxun Jin; Il-Keun Kong (Theriogenology, 2024)

Sheep bone valorization: Enhancing gastronomic sustainability through hydroxyapatite-enriched potato wedges - Saba Liaqat; Zaheer Ahmed; Muhammad Usama Umer; Qasim Ali; Muhammad Farooq Mustafa; Ifra Ferheen; Muhammad Waseem (International Journal of Gastronomy and Food Science, 2024)

Zinc Oxide Nanoparticles Significant Role in Poultry and Novel Toxicological Mechanisms - Arjmand Fatima; Tean Zaheer; Kaushik Pal; Rao Zahid Abbas; Tayyaba Akhtar; Sultan Ali; Muhammad Shahid Mahmood (Biological Trace Element Research, 2024)

Serological detection of important pepper viruses and characterisation of pepper mild mottle virus in Saudi Arabia - Zaheer Khalid; Mahmoud Ahmed Amer; Muhammad Amir; Khadim Hussain; Ibrahim Al-Shahwan; Mohammed Ali Al-Saleh (Australasian Plant Pathology, 2024)

Effect of crop combination on yield performance, nutrient uptake, and land use advantage of cereal/legume intercropping systems - Muhammad Ali Raza; Wang Zhiqi; Hassan Shehryar Yasin; Hina Gul; Ruijun Qin; Sana Ur Rehman; Aqib Mahmood; Zafar Iqbal; Zaheer Ahmed; Shuanglong Luo; Chen Juan; Xue Liang; et al. (Field Crops Research, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

Using walnut shells as low-cost adsorbent materials in an anaerobic filter medium of a De-centralized wastewater treatment system (DEWATS) - Muhammad Zaheer; Muhammad Shaham Ali; Ning Huang; Muhammad Aqeel Ashraf (Chemosphere, 2023)

The impact of CSR and green consumption on consumer satisfaction and loyalty: moderating role of ethical beliefs - Sohail Ahmad; Muhammad Irfan Shakir; Afshan Azam; Shahid Mahmood; Qingyu Zhang; Zaheer Ahmad (Environmental Science and Pollution Research, 2023)

Bio-ecology and the management of Chenopodium murale L.: A problematic weed in Asia - Ali Raza; Hafiz Haider Ali; Muhammad Saqlain Zaheer; Javaid Iqbal; Mahmoud Fathy Seleiman; Jaffar Sattar; Basharat Ali; Shumaila Khan; Tuba Arjumend; Bhagirath Singh Chauhan (Crop Protection, 2023)

Impact of biochar amendments on copper mobility, phytotoxicity, photosynthesis and mineral fluxes on (Zea mays L.) in contaminated soils - Zainul Abideen; Hans-Werner Koyro; Faisal Zulfiqar; Anam Moosa; Sarwat Ghulam Rasool; Muhammad Zaheer Ahmad; Muhammad Ahsan Altaf; Nadia Sharif; Ali El-Keblawy (South African Journal of Botany, 2023)

Sedimentology and reservoir characteristics of Jurassic Samanasuk Formation of Salt Range and Hazara areas, Upper Indus Basin, Pakistan - Syed Umair Ali; Syed Kamran Ali; Khawaja Umair Majeed; Muhammad Haris; Muhammad Zaheer; Tariq Mehmood (Arabian Journal of Geosciences, 2023)

Supplementation of Moringa based zinc oxide nanoparticles mitigates salt stress in Celosia argentea through reduced chloride (Cl −) uptake and modulation in physiochemical attributes - Musarrat Ramzan; Nabeera Naveed; Muhammad Zaheer Ahmed; Hina Ashraf; Anis Ali Shah; Muhammad Jamil; Zahoor Ahmad; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2023)

Exogenous application of glutathione and gamma amino-butyric acid alleviates salt stress through improvement in antioxidative defense system and modulation of CaXTHs stress-related genes - Musarrat Ramzan; Anis Ali Shah; Muhammad Zaheer Ahmed; Muhammad Adnan Bukhari; Liaqat Ali; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2023)

Advances in limitations and opportunities of clean biofuel production to promote decarbonization - Ali Sarosh Khawaja; Muhammad Ayman Zaheer; Ali Ahmad; Asif Ali Mirani; Zulfiqar Ali (Fuel, 2023)

Knowledge, attitude, and perceptions about cancer genetic testing in clinical practice in Karachi, Pakistan - Shameel Shafqat; Masooma Naseem; Masooma Rana; Zehra Naseem; Warda Ahmed; Muhammad Daniyal Musharraf; Arisha Zaheer; Ahmed Safiullah Shaikh; Muhammad Bazil Musharraf; Mahnoor Niaz; Saifullah Khan; Rabiya Irfan; et al. (Journal of Community Genetics, 2023)

Architectural complexities and morphological variations of the indus fan and its elements: Understanding of the turbidite system through seismic characterization - Ehsan ul Haq; Ji Youliang; Hadayat Ullah; Khurram Shahzad; Nisar Ahmed; Saad Ahmed Mashwani; Muhammad Zaheer (Marine and Petroleum Geology, 2023)

Syntheses, in vitro, and in silico studies of rhodanine-based schiff bases as potential α-amylase inhibitors and radicals (DPPH and ABTS) scavengers - Samuel Attah Egu; Irfan Ali; Khalid Mohammed Khan; Sridevi Chigurupati; Urooj Qureshi; Uzma Salar; Muhammad Taha; Shatha Ghazi Felemban; Vijayan Venugopal; Zaheer Ul-Haq (Molecular Diversity, 2023)

Bioplastics from waste biomass of marine and poultry industries - Amna Arif; Farrukh Azeem; Ijaz Rasul; Muhammad Hussnain Siddique; Muhammad Zubair; Faizan Muneer; Warda Zaheer; Habibullah Nadeem (Journal of Biosciences, 2023)

Assessment of knowledge, perception, practices and drivers of antimicrobial resistance and antimicrobial usage among veterinarians in Pakistan - Ayesha Saman; Mamoona Chaudhry; Muhammad Ijaz; Waseem Shaukat; Muhammad Usman Zaheer; Ana Mateus; Abdul Rehman (Preventive Veterinary Medicine, 2023)

Investigating the nexus between critical success factors, supportive leadership, and entrepreneurial success: evidence from the renewable energy projects - Muttahir Hussain; Samma Faiz Rasool; Wang Xuetong; Muhammad Zaheer Asghar; Abdulmohsen Saleh A. Alalshiekh (Environmental Science and Pollution Research, 2023)

Biodegradation of macro- and micro-plastics in environment: A review on mechanism, toxicity, and future perspectives - Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Zaheer; Wenbiao Jin; Lei Yang (Science of The Total Environment, 2023)

A comparative study of different types of the inversion algorithms for the reservoir characterization of Mehar Block, Pakistan - Nizam Ud Din; Muhammad Kashif; Jamil Khan; Zaheer Hussain; Jose N. Mendez; Wasif Saeed (Arabian Journal of Geosciences, 2023)

Discovering patterns in the topography of existing settlements: the case of the China-Pakistan Economic Corridor (CPEC) route - Ahsen Maqsoom; Bilal Aslam; Umer Khalil; Sheheryar Azam; Zaheer Abbas Kazmi; Muhammad Usman Arif Rana (Arabian Journal of Geosciences, 2023)

Urban Heat Island vulnerability mapping using advanced GIS data and tools - Paras Sidiqui; Phillip B Roös; Murray Herron; David S Jones; Emma Duncan; Ali Jalali; Zaheer Allam; Bryan J Roberts; Alexander Schmidt; Muhammad Atiq Ur Rehman Tariq; Ashfaq Ahmed Shah; Nasir Abbas Khan; et al. (Journal of Earth System Science, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Sedimentology and Diagenesis of the Early–Middle Eocene Carbonate Deposits of the Ceno-Tethys Ocean - Ahmer Bilal; Renchao Yang; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Muhammad Zaheer; George Kontakiotis (Journal of Marine Science and Engineering, 2022)
An integrated study based on field observation, petrography, and scanning electron microscopy (SEM) on the Early–Middle Eocene carbonate rocks has been carried out, which were deposited in the Ceno-Tethys Ocean. The study area of the Yadgaar Section lies on the eastern margin of the Upper Indus Basin, Pakistan. The Early–Middle Eocene Margalla Hill Limestone and Chorgali Formation act as reservoir rocks in other parts of the basin and are also present in the Yadgaar Section. The lack of comprehensive study in this area makes these reservoir rocks highly attractive for sedimentological evaluations and future exploration of hydrocarbons. The Early–Middle Eocene carbonate rocks are divided into nine microfacies: dolomicritic foraminiferal mudstone–wackestone microfacies (EMI); green algae dominated, mixed foraminiferal wackestone–packstone microfacies (EMII); ostracod, green algae and gypsum dominating mudstone–wackestone microfacies (EMIII); algae and mixed foraminiferal wackestone–packstone microfacies (EMIV); Nummulites dominating mudstone–wackestone microfacies (EMV); algal limestone mudstone microfacies (EMVI); Assilina bed wackestone–packstone microfacies (EMVII); micritized larger benthic foraminiferal wackestone–packstone microfacies (EMVIII); and algal limestone, mudstone microfacies (EMIX). The transgressive-regressive environment in the Ceno-Tethys Ocean leads to the deposition of these microfacies in the platform interior, open marine platform, platform edge, platform margin reef, toe of the slope apron, arid–humid platform interior, platform edge, open marine platform interior, and restricted marine platform interior, respectively. Initial post-depositional diagenetic stages are identified from the base to the top of the strata by their respective cement types, i.e., the base–lower middle part of the strata demonstrates an eogenetic sub-stage with the appearance of drusy cement, the middle section indicates a mesogenetic sub-stage by the appearance of blocky cement, while the top portion again reveals an eogenetic sub-stage of diagenesis by the presence of drusy and blocky types of cement. The ascending–descending hierarchy of cement generations is directly proportional to the grade of diagenesis from the base to the top of the carbonate strata. Variable diagenetic effects on the various microfacies also increase the secondary porosity range and enhance the reservoir characteristics of the Formations. The presence of foraminifera microfossils determined that these carbonate formations date from the Early–Middle Eocene.

Mixing tannery effluent had fertilizing effect on growth, nutrient accumulation, and photosynthetic capacity of some cucurbitaceous vegetables: A little help from foe - Muhammad Zaheer; Zafar Ullah Zafar; Habib-ur-Rehman Athar; Hussan Bano; Misbah Amir; Ayesha Khalid; Hamid Manzoor; Muhammad Javed; Muhammad Iqbal; Chukwuma C. Ogbaga; Muhammad Kamran Qureshi (Environmental Science and Pollution Research, 2022)

Simultaneous adsorptive removal of three fluoroquinolones using humic acid modified hydrogel beads - Muhammad Zaheer Afzal; Salma Hameed; Muhammad Mohiuddin; Asim Abbasi (Environmental Science and Pollution Research, 2022)

Synergetic Efficacy of Amending Pb-Polluted Soil with P-Loaded Jujube (Ziziphus mauritiana) Twigs Biochar and Foliar Chitosan Application for Reducing Pb Distribution in Moringa Leaf Extract and Improving Its Anti-cancer Potential - Bilal Rasool; Mahmood-ur-Rahman; Muhammad Zubair; Muhammad Asaf Khan; Pia Muhammad Adnan Ramzani; Agnieszka Dradrach; Veysel Turan; Muhammad Iqbal; Shahbaz Ali Khan; Hafiz Muhammad Tauqeer; Muniba Farhad; Zaheer Abbas Virk; et al. (Water, Air, & Soil Pollution, 2022)

Salt tolerance screening of a newly developed wheat variety (AZRC-DK-84) in saline environment using halophytic grass (Cenchrus penisettiformis) as a test model - Basit Ali; Muhammad Umar; Muhammad Azeem; Zaheer Uddin; Zamin Shaheed Siddiqui (Acta Physiologiae Plantarum, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Factors associated with cycle threshold values (Ct-values) of SARS-CoV2-rRT-PCR - Naila Shoaib; Naila Noureen; Arwa Faisal; Muhammad Zaheer; Muhammad Imran; Ali Ahsan; Rimsha Munir; Nousheen Zaidi (Molecular Biology Reports, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

Evaluating pollution damage function through carbon pricing, renewable energy demand, and cleaner technologies in China: blue versus green economy - Muhammad Zaheer Akhtar; Khalid Zaman; Faheem Ur Rehman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Humic acid overcomes salinity barriers and stimulates growth of Urochondra setulosa by altering ion-flux and photochemistry - Sonia Bano; Muhammad Zaheer Ahmed; Zainul Abideen; Muhammad Qasim; Bilquees Gul; Nasir Uddin Khan (Acta Physiologiae Plantarum, 2022)

Calculation of urban solar radiation based on simulation and fitting of ASHRAE model constants - Atteeq Razzak; Zaheer Uddin; Muhammad Jawed Iqbal; Khan Alam (Arabian Journal of Geosciences, 2022)

Characterization of new COBRA like (COBL) genes in wheat (Triticum aestivum) and their expression analysis under drought stress - Muhammad Zaheer; Shoaib Ur Rehman; Sultan Habibullah Khan; Shahmeer Shahid; Awais Rasheed; Rabia Naz; Muhammad Sajjad (Molecular Biology Reports, 2022)

Integrated support vector regressor and hybrid neural network techniques for earthquake prediction along Chaman fault, Baluchistan - Umer Khalil; Bilal Aslam; Zaheer Abbas Kazmi; Ahsen Maqsoom; Muhammad Irshad Qureshi; Sheheryar Azam; Ahsan Nawaz (Arabian Journal of Geosciences, 2021)

SNPs at 3′UTR of APOL1 and miR-6741-3p target sites associated with kidney diseases more susceptible to SARS-COV-2 infection: in silco and in vitro studies - Muhammad Safdar; Muhammad Sajjad Khan; Abdulkarim Yasin Karim; Shwan Ali Omar; Shukur Wasman Smail; Muhammad Saeed; Sana Zaheer; Mazhar Ali; Bilal Ahmad; Muhammad Tasleem; Yasmeen Junejo (Mammalian Genome, 2021)

Helminth protection against type-1 diabetes: an insight into immunomodulatory effect of helminth-induced infection - Muhammad Adnan Sabir Mughal; Muhammad Kasib Khan; Zaheer Abbas; Rao Zahid Abbas; Hammad ur Rehman Bajwa; Abdullah Khalid Chatha; Muhammad Imran; Zia ud Din Sindhu; Asghar Abbas; Arsalan Zafar; Muhammad Nadeem (Molecular Biology Reports, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Benzilydene and thiourea derivatives as new classes of carbonic anhydrase inhibitors: an in vitro and molecular docking study - Shama Qaiser; Mohammad S. Mubarak; Sajda Ashraf; Muhammad Saleem; Zaheer Ul-Haq; Muhammad Safdar; Abdur Rauf; Tareq Abu-Izneid; Malak I. Qadri; Aneela Maalik (Medicinal Chemistry Research, 2021)

Biology-oriented drug synthesis (BIODS), in vitro urease inhibitory activity, and in silico studies on ibuprofen derivatives - Faiza Seraj; Kanwal; Khalid Mohammed Khan; Ajmal Khan; Muhammad Ali; Ruqaiya Khalil; Zaheer Ul-Haq; Shehryar Hameed; Muhammad Taha; Uzma Salar; Shahnaz Perveen (Molecular Diversity, 2021)

Growth regulation of Desmostachya bipinnata by organ-specific biomass, water relations, and ion allocation responses to improve salt resistance - Muhammad Yousuf Adnan; Tabassum Hussain; Muhammad Zaheer Ahmed; Bilquees Gul; M. Ajmal Khan; Brent L. Nielsen (Acta Physiologiae Plantarum, 2021)

Synthesis, urease inhibition screening and molecular docking studies of piperonal based imine derivatives - Obaid-ur-Rahman Abid; Saima Daud; Asma Sardar; Wajid Rehman; Abdul Wadood; Ashfaq Ur Rehman; Toheed Akhter; Iram Bibi; Zaheer Ahmad; Muhammad Yasir (Medicinal Chemistry Research, 2021)

Interactive role of zinc and iron lysine on Spinacia oleracea L. growth, photosynthesis and antioxidant capacity irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Hamzah Saleem; Mohsin Ali; Muhammad Riaz; Sehar Javed; Anam Sehar; Zohaib Abbas; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Physiology and Molecular Biology of Plants, 2020)

The Relevance of SNPs at 3′UTR Region of CASP7 and miR-371b-5p Associated Diseases: A Computational Analysis - Muhammad Safdar; Sana Zaheer; Rozhgar A. Khailany; Sadaf Parvez; Muhammad Naveed; Piplu Bhuiyan; Mehmet Ozaslan; Rebaz Moatasam; Mustafa S. Al-Attar; Musarrat Abbas Khan; Yasmeen Junejo (Cell Biochemistry and Biophysics, 2020)

Anti-urease and cytotoxic activity of 1-Nitro-2-phenylethane and Nerolidol; two major compounds isolated from the seeds of Dennettia tripetala - Samuel E. Ugheighele; Kate E. Imafidon; Muhammad I. Choudhary; Ahmed Shakil; Majid Khan; Zaid A. Sherwani; Zaheer Ul-Haq (Medicinal Chemistry Research, 2020)

Long-segment transverse myelitis in an immunocompetent patient due to varicella zoster virus reactivation - Tanvi Goyal; Muhammad Zaheer; Anirudh Goyal; Zubair Khan (Journal of NeuroVirology, 2020)

Phytotoxic analysis of coastal medicinal plants and quantification of phenolic compounds using HPLC - Muhammad Qasim; Yoshiharu Fujii; Muhammad Zaheer Ahmed; Irfan Aziz; Kazuo N. Watanabe; M. Ajmal Khan (Plant Biosystems, 2019)

Zinc-lysine prevents chromium-induced morphological, photosynthetic, and oxidative alterations in spinach irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Rizwan; Firdaus-e- Bareen; Zohaib Abbas; Syed Asad Hussain Bukhari; Leonard Wijaya; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Arsenic contamination, subsequent water toxicity, and associated public health risks in the lower Indus plain, Sindh province, Pakistan - Asfandyar Shahab; Shihua Qi; Muhammad Zaheer (Environmental Science and Pollution Research, 2019)

Membrane biofouling retardation by zwitterionic peptide and its impact on the bacterial adhesion - Si-Yu Wang; Deng-Cheng Han; Chao Song; Meng-Na Li; Muhammad Zaheer Afzal; Shu-Guang Wang; Xue-Fei Sun (Environmental Science and Pollution Research, 2019)

A critical review of mechanisms involved in the adsorption of organic and inorganic contaminants through biochar - Zohaib Abbas; Shafaqat Ali; Muhammad Rizwan; Ihsan Elahi Zaheer; Afifa Malik; Muhammad Ahsan Riaz; Muhammad Rizwan Shahid; Muhammad Zia ur Rehman; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Alkali-Activated Boiler Fly Ash for Ni(II) Removal: Characterization and Parametric Study - Muhammad Samiullah; Zaheer Aslam; Adeem Ghaffar Rana; Aamir Abbas; Waqar Ahmad (Water, Air, & Soil Pollution, 2018)

Petrography, provenance, diaganesis and depositional environment of Murree Formation in Jhelum Valley, Sub Himalayas, Azad Jammu and Kashmir, Pakistan - Muhammad Zaheer; Muhammad Sabir Khan; Muhammad Saleem Mughal; Noman Abbasi (Arabian Journal of Geosciences, 2017)

Foliar application of aspartic acid lowers cadmium uptake and Cd-induced oxidative stress in rice under Cd stress - Muhammad Rizwan; Shafaqat Ali; Muhammad Zaheer Akbar; Muhammad Bilal Shakoor; Abid Mahmood; Wajid Ishaque; Afzal Hussain (Environmental Science and Pollution Research, 2017)

Use of Maize (Zea mays L.) for phytomanagement of Cd-contaminated soils: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Zia-ur-Rehman; Zaheer Abbas; Fakhir Hannan (Environmental Geochemistry and Health, 2017)

Effect of different amendments on rice (Oryza sativa L.) growth, yield, nutrient uptake and grain quality in Ni-contaminated soil - Pia Muhammad Adnan Ramzani; Waqas-ud-Din Khan; Muhammad Iqbal; Salma Kausar; Shafaqat Ali; Muhammad Rizwan; Zaheer Abbas Virk (Environmental Science and Pollution Research, 2016)

Hydrological response to environment change in Himalayan watersheds: Assessment from integrated modeling approach - Zulfiqar Ahmad; Arshad Ashraf; Muhammad Zaheer; Humaira Bashir (Journal of Mountain Science, 2015)

Perspective of Surface Active Agents in Baking Industry: An Overview - Asif Ahmad; Nazish Arshad; Zaheer Ahmed; Muhammad Shahbaz Bhatti; Tahir Zahoor; Nomana Anjum; Hajra Ahmad; Asma Afreen (Critical Reviews in Food Science and Nutrition, 2014)

Erratum to: Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammed Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammad Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Development and Evaluation of Hydrophilic Colloid Matrix of Famotidine Tablets - Muhammad Harris Shoaib; Saniah Al Sabah Siddiqi; Rabia Ismail Yousuf; Kamran Zaheer; Muhammad Hanif; Saeed Rehana; Sabahat Jabeen (AAPS PharmSciTech, 2010)

Monoterpene glycosides from Indigofera hetrantha - Sajid Mehmood; Aziz-Ur-Rahman; Zaheer Ahmad; Nighat Afza; Abdul Malik; Habib Ahmad; Muhammad Iqbal Choudhary (Natural Product Research, 2008)

Successful computer guided planned synthesis of (4R)-thiazolidine carboxylic acid and its 2-substituted analogues as urease inhibitors - Khalid Mohammed Khan; Zia Ullah; Muhammad Arif Lodhi; Muhammad Ali; Muhammad Iqbal Choudhary; Atta ur Rahman; Zaheer ul Haq (Molecular Diversity, 2006)